2016
DOI: 10.1364/oe.24.012107
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental analysis of excessively tilted fiber gratings

Abstract: We have theoretically and experimentally investigated the dual-peak feature of tilted fiber gratings with excessively tilted structure (named as Ex-TFGs). We have explained the dual-peak feature by solving eigenvalue equations for TM0m and TE0m of a circular waveguide, in which the TE (transverse electric) and TM (transverse magnetic) core modes are coupled into TE and TM cladding modes, respectively. Meanwhile, in the experiment, we have verified that one of the dual peaks at the shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…As shown in Fig. 2(c), with the resonant wavelength increase, the separation linearly increases, indicating wavelength dependent feature, which can be explained by the increasing effective index difference between the TM and TE modes [18]. The tuning characteristics of polarization of the Ex-TFG cladding modes with SRI variation were experimentally examined by using a series of refractive index liquids (from Cargille Labs) ranging from 1.300 to 1.400 with interval of 0.01.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…As shown in Fig. 2(c), with the resonant wavelength increase, the separation linearly increases, indicating wavelength dependent feature, which can be explained by the increasing effective index difference between the TM and TE modes [18]. The tuning characteristics of polarization of the Ex-TFG cladding modes with SRI variation were experimentally examined by using a series of refractive index liquids (from Cargille Labs) ranging from 1.300 to 1.400 with interval of 0.01.…”
mentioning
confidence: 88%
“…By examining the spectral evolution under different polarizations, it was found that the TE light from the cladding modes of all orders is more coupled into graphene layer, which attests to polarization-sensitive absorption of graphene for all leaky modes [3,4]. It is apparent that the change of coupling intensity of TE polarization is always larger than that of TM for all cladding modes [18], as shown in Fig. 2(b).…”
mentioning
confidence: 92%
“…This feature makes small-angle TFGs an excellent candidate for sensing applications [24]. On the other hand, in excessively tilted fiber gratings (Ex-TFGs) [25], the fiber core mode can be coupled into forward propagating cladding modes. Due to birefringent mode coupling, Ex-TFGs have been applied in refractive index sensing with extremely low thermal cross sensitivity [26].…”
Section: Principlementioning
confidence: 99%
“…Usually, tilt angles of the fabricated Ex-TFGs were from 79° to 83°. The surrounding refractive index (RI) sensitivity of the sensor is affected by a tilt angle increase, but the influence is low in this range [22]. In order to guarantee the claddingmode resonance to appear in the ~1550 nm wavelength range, 81° tilt angle was selected.…”
Section: Fabrication Of Ex-tfgs and Apparatusmentioning
confidence: 99%